Silicon nitride powder and method for producing silicon nitride sintered body
Patent Information
- Application Number
- CN202580024096.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-26
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies struggle to manufacture silicon nitride sintered bodies with high insulation and heat dissipation properties, particularly due to deficiencies in the selection of silicon nitride powder and manufacturing methods.
Silicon nitride powder with an isoelectric point of pH 7–9, an α-saturation rate of 90–97%, and a pH of 2–4 when the zeta potential reaches its maximum positive zeta potential is used. Through specific manufacturing processes including nitriding of metallic silicon, coarse grinding, fine grinding, acid treatment, and cleaning, the particle size, specific surface area, and impurity content of the powder are controlled, and appropriate sintering conditions are combined to manufacture silicon nitride sintered bodies.
A silicon nitride sintered body with excellent insulation and heat dissipation properties was achieved, with an insulation breakdown voltage of over 5kV and a thermal conductivity of over 50W/(m·K), meeting the requirements of high-performance materials.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to silicon nitride powder and a method for manufacturing silicon nitride sintered bodies.
[0002] This application claims priority based on Japanese Patent Application No. 2024-057571, filed in Japan on March 29, 2024, the contents of which are incorporated herein by reference. Background Technology
[0003] Silicon nitride sintered bodies are materials with excellent strength, hardness, toughness, heat resistance, corrosion resistance, and thermal shock resistance. Therefore, they are used in various industrial components such as die-casting machines and melting furnaces, as well as insulating substrates for automotive parts. Regarding silicon nitride powder as a raw material for silicon nitride sintered bodies, silicon nitride powder with a high alpha saturation rate is used to obtain high-quality sintered bodies.
[0004] Research is also underway on the use of silicon nitride substrates as insulating substrates for power modules in automobiles and machine tools. For example, Patent Document 1 proposes the use of silicon nitride substrates in aluminum-ceramic bonding substrates. In such applications, high insulation and heat dissipation are required.
[0005] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2011-077546 Summary of the Invention
[0006] The problem that the invention aims to solve The purpose of this invention is to provide a novel silicon nitride powder capable of manufacturing sintered bodies with excellent insulation and heat dissipation properties, and a method for manufacturing silicon nitride sintered bodies using the same.
[0007] Methods for solving problems The present invention has the following aspects.
[0008] [1] Silicon nitride powder, which has an isoelectric point at pH 7 to 9.
[0009] [2] The silicon nitride powder described in [1] has an α-saturation rate of 90-97%.
[0010] [3] The silicon nitride powder described in [1] or [2] has a pH of 2 to 4 at which it reaches the maximum positive Zeta potential.
[0011] [4] The silicon nitride powder as described in [3], wherein the Zeta potential at pH 1.5 is 30 to 45 mV.
[0012] [5] A method for manufacturing a silicon nitride sintered body, wherein a sintering raw material comprising silicon nitride powder as described in any one of [1] to [4] above is shaped and sintered.
[0013] [6] A silicon nitride sintered body, which is manufactured using the manufacturing method described above [5].
[0014] [7] The silicon nitride sintered body as described in [6] has an insulation breakdown voltage of 5 kV or more, preferably 9 kV or more, as measured by the method described in the embodiments described later.
[0015] [8] The silicon nitride sintered body as described in [6] or [7] has a thermal conductivity of 50 W / (m·K) or more, preferably 70 W / (m·K) or more, as measured by the method described in the examples described later.
[0016] The effects of the invention According to the present invention, silicon nitride powder that can be used to manufacture sintered bodies with excellent insulation and heat dissipation properties can be provided.
[0017] Furthermore, according to the present invention, a silicon nitride sintered body with excellent insulation and heat dissipation can be provided. Detailed Implementation
[0018] The meanings and definitions of the terms used in this specification are as follows.
[0019] The range indicated by "~" refers to the range of values with the values before and after "~" as the lower and upper limits. In this specification, the upper and lower limits can be combined arbitrarily.
[0020] The "isoelectric point" refers to the pH at which the Zeta potential becomes 0.
[0021] The term "Zeta potential" refers to the value measured by the electroacoustic method (ESA). The electroacoustic method involves applying an alternating voltage to a dispersion of silicon nitride powder and measuring the Zeta potential based on the ESA signal of the ultrasonic waves generated by particle vibration.
[0022] "Average particle size" refers to the 50% cumulative volume particle size (hereinafter also referred to as "D") calculated based on the particle size distribution of the powder. 50 The particle size distribution can be obtained in accordance with JIS R 1629:1997 "Method for determination of particle size distribution of fine ceramic raw materials based on laser diffraction and scattering".
[0023] The term "specific surface area" refers to the value determined by the BET single-point method using nitrogen gas, in accordance with JIS R 1626:1996 "Determination of specific surface area of fine ceramic powders by gas adsorption BET method".
[0024] "α-SiNdRatio" refers to the ratio of α-silicon nitride to silicon nitride as a whole, and is calculated by the following formula 1.
[0025] α-conversion rate (%) = [I α(102) +I α(210) ] / [I α(102) +I α(210) +I β(101) +I β(210) ]×100 …Formula 1 In the aforementioned Equation 1, I α(102) I represents the intensity of the diffraction peak on the (102) plane of the α phase of silicon nitride. α(210) I represents the intensity of the diffraction peak on the (210) plane of the α phase of silicon nitride. β(101) I represents the intensity of the diffraction peak on the (102) plane of the β phase of silicon nitride. β(210) The intensity of the diffraction peaks on the (210) plane of the β phase of silicon nitride. Each diffraction peak can be obtained from the XRD pattern obtained by X-ray powder diffraction.
[0026] The iron content of the silicon nitride powder was determined using a fluorescence X-ray analysis device (manufactured by Rigaku Corporation, device name: PrimasII).
[0027] The chlorine and fluorine content of silicon nitride powder is based on the following values, which are obtained by dissolving the gas generated by heating silicon nitride powder in water and determining the amount of Cl ions and F ions in the water using ion chromatography. These values are sometimes referred to as "chlorine (Cl) content" and "fluorine (F) content," respectively.
[0028] The oxygen content of silicon nitride powder is obtained by heating the silicon nitride powder to 2000°C in a helium atmosphere and detecting the oxygen content in the released gas.
[0029] Silicon nitride powder The silicon nitride powder of this embodiment (hereinafter also referred to as "this powder") has an isoelectric point at pH 7 to 9. That is, the pH at which the zeta potential of this powder is 0 exists at least in the pH range of 7 to 9. In addition, it may also have an isoelectric point outside the pH range of 7 to 9. For example, the isoelectric point may also exist below pH 1.
[0030] The powder preferably has an isoelectric point in the range of pH 7.2 to 8.8, and more preferably in the range of pH 7.4 to 8.6.
[0031] The isoelectric point of silicon nitride powder can be controlled by the manufacturing method and conditions of silicon nitride powder.
[0032] Regarding the Zeta potential of this powder, the pH at which the maximum positive Zeta potential is achieved is preferably 2 to 4. That is, in a curve plotted with the Zeta potential of this powder on the vertical axis and pH on the horizontal axis, a maximum value is preferably found in the pH range of 2 to 4.
[0033] Regarding the zeta potential of this powder, it is more preferable that the pH at which the maximum positive zeta potential is reached is 2 to 4, and the zeta potential at pH 1.5 is 30 to 45 mV.
[0034] The specific surface area of this powder is preferably 5-15 m². 2 / g, more preferably 6-14m 2 / g, more preferably 7-13m 2 / g.
[0035] The specific surface area of silicon nitride powder can be controlled, for example, by adjusting the pulverization conditions during the manufacturing of silicon nitride powder.
[0036] The D of this powder 50 Preferably, the particle size is 1 μm or less, more preferably 0.9 μm or less, and even more preferably 0.8 μm or less. The D-type of silicon nitride powder... 50 There is no particular limitation on the lower limit value. For example, it can be above 0.4μm, above 0.5μm, or above 0.6μm.
[0037] The aforementioned upper and lower limits can be combined appropriately. For example, the D of this powder 50 It can be 0.4μm or higher than 0.9μm, 0.5μm or higher than 0.9μm, or 0.6μm or higher than 0.8μm.
[0038] If the D of this powder 50 If the value is below the aforementioned upper limit, it is easy to manufacture silicon nitride sintered bodies. The D of silicon nitride powder... 50 For example, this can be controlled by adjusting the pulverization method, pulverization conditions, and grading conditions during the manufacture of silicon nitride powder.
[0039] The content of iron relative to the total mass of the powder (Fe content) is preferably 300 ppm by mass or less, more preferably 200 ppm by mass or less, and even more preferably 150 ppm by mass or less. The lower limit of the iron content relative to the total mass of the powder is not particularly limited; for example, it can be 10 ppm by mass or more, 30 ppm by mass or more, 50 ppm by mass or more, or 100 ppm by mass or more.
[0040] The aforementioned upper and lower limits can be appropriately combined. For example, the aforementioned Fe content can be 10 ppm to 300 ppm by mass, 30 ppm to 200 ppm by mass, 50 ppm to 150 ppm by mass, or 100 ppm to 150 ppm by mass. Alternatively, the aforementioned Fe content can be 120 to 130 ppm by mass. If the iron content relative to the total mass of the powder is below the aforementioned upper limit, the thermal conductivity and mechanical properties of the silicon nitride sintered body manufactured using this powder are easily improved.
[0041] Iron in silicon nitride powder is an impurity introduced during processes such as the wear and tear of components in a pulverizer used in the manufacturing of silicon nitride powder. The iron content in silicon nitride powder can be controlled by the processing methods and conditions used in processes to remove impurities (e.g., acid treatment, cleaning, etc.).
[0042] The α-oxidation rate of this powder is preferably 88% or more, more preferably 89% or more, and even more preferably 90% or more. There is no particular upper limit to the α-oxidation rate of this powder; for example, it can be 97% or less, 95% or less, or 93% or less.
[0043] The above upper and lower limits can be combined appropriately. For example, the α-oxidation rate of this powder can be above 88% and below 97%, above 89% and below 95%, or above 90% and below 93%.
[0044] If the α-saturation of this powder is above the aforementioned lower limit, then when using this powder to manufacture a sintered body, grain growth during sintering can be promoted. As a result, a sufficiently dense silicon nitride sintered body can be manufactured. Therefore, a silicon nitride sintered body with superior high-temperature strength and high thermal conductivity can be obtained.
[0045] For example, in the case of synthesizing silicon nitride using the direct nitriding method, the α-oxidation rate of the silicon nitride powder is essentially determined by the nitriding reaction conditions of the silicon powder.
[0046] The oxygen content of this powder is preferably 0.5 to 1.5% by mass, more preferably 0.6 to 1.4% by mass, and even more preferably 0.7 to 1.3% by mass.
[0047] If the oxygen content of this powder is within the above-mentioned range, the effect of the present invention will be improved, and it is preferred from this perspective.
[0048] The oxygen content of silicon nitride powder originates from the oxides present in the primary particles of silicon nitride. The oxygen content of silicon nitride powder can be controlled by adjusting the conditions of the oxidation processes during its manufacturing. For example, it can be controlled by adjusting the composition of the firing atmosphere in the firing process and the concentration of acidic substances used in the acid treatment process.
[0049] This powder may contain elements other than silicon, nitrogen, and oxygen. Examples of other elements include calcium derived from fluorite, halogens, iron derived from the aforementioned metal powder, the aforementioned metal compound powder, and the pulverizing apparatus, and other metal elements other than silicon. The total content of other elements relative to the total mass of this powder is preferably 1.0% by mass or less, more preferably 0.8% by mass or less, and even more preferably 0.5% by mass or less.
[0050] Method for manufacturing silicon nitride powder The method for manufacturing this powder is not particularly limited. Preferably, this powder is a silicon nitride powder manufactured, for example, through a process of pulverizing silicon nitride obtained by direct nitriding.
[0051] The grinding of silicon nitride can be broadly divided into dry grinding and wet grinding. In the case of wet grinding, it is easier to achieve micronization.
[0052] The powder is preferably silicon nitride powder manufactured by a silicon nitriding process and a pulverizing process of pulverizing the silicon nitride obtained by the silicon nitriding process. The aforementioned pulverizing process preferably includes a coarse pulverizing process to obtain coarse powder and a micro-pulverizing process of subsequently micronizing by wet pulverization.
[0053] Hereinafter, “coarse powder” refers to powder with an average particle size of more than 1 μm.
[0054] While wet milling yields silicon nitride powder with small particle sizes, the components of the wet mill sometimes experience wear and tear during the process. Therefore, impurities (e.g., iron) originating from the components of the aforementioned wet mill may sometimes contaminate the silicon nitride powder. Furthermore, in wet milling, because the process is carried out in water, some of the silicon nitride reacts with the water, resulting in the formation of silicon dioxide. Such impurities reduce the quality of the silicon nitride sintered body manufactured from the silicon nitride powder. Therefore, it is preferable to perform an acid treatment step by immersing the wet-milled silicon nitride powder in an acidic solution to dissolve the impurities, followed by a cleaning step that involves solid-liquid separation to remove the dissolved impurities. This powder is preferably silicon nitride powder manufactured through the aforementioned acid treatment and cleaning steps.
[0055] In the cleaning process following acid treatment, the treated liquid containing silicon nitride powder, acidic substances, and impurities is fed to a solid-liquid separator to obtain a composition containing silicon nitride powder with reduced acidic substances and impurities. The obtained composition containing silicon nitride powder is dried to obtain acid-treated silicon nitride powder.
[0056] The powder is preferably silicon nitride powder manufactured by the following coagulation and filtration process, in which a filtration device is used as the aforementioned solid-liquid separator, and a coagulant is added to the aforementioned liquid to be treated for filtration.
[0057] (The nitriding process of metallic silicon) In the nitriding process of metallic silicon, the raw material powder containing metallic silicon powder is nitrided by firing in an atmosphere containing nitrogen.
[0058] As metallic silicon powder, powder obtained by crushing metallic silicon blocks or particles can be used. Examples of crushing devices include hammer mills, pin mills, ball mills, vibratory mills, and jet mills.
[0059] The purity of the metallic silicon powder is preferably 98% by mass or more, more preferably 99% by mass or more. The metallic silicon powder may sometimes contain impurities originating from lumps or particles of metallic silicon, or impurities originating from the grinding device.
[0060] Metallic silicon powder can be used directly as the raw material powder, or it can be prepared by combining metallic silicon powder with fluorite and other metal powders or metal compounds (e.g., chromium compounds, nickel compounds). The content of metallic silicon powder relative to 100 parts by mass of the raw material powder is preferably 92 parts by mass or more, more preferably 95 parts by mass or more, and even more preferably 97 parts by mass or more.
[0061] When the raw material powder contains fluorite (CaF2), the fluorite content relative to 100 parts by mass of silicon metal powder is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.8 parts by mass or more. If the fluorite content is above the aforementioned lower limit, silicon metal nitriding is easier to perform. The fluorite content relative to 100 parts by mass of silicon metal powder is preferably 3.0 parts by mass or less, more preferably 2.0 parts by mass or less, and even more preferably 1.5 parts by mass or less. If the fluorite content is below the aforementioned upper limit, the calcium and fluorine content in the obtained silicon nitride powder can be reduced.
[0062] In the nitriding process of metallic silicon, the raw material powder can be sintered directly, or it can be formed into a molded body before sintering. Nitriding involves sintering the raw material powder or a molded body of the raw material powder (hereinafter also referred to as "raw material powder, etc.") in a sintering furnace under a nitrogen atmosphere. The sintering furnace can be a continuous furnace or a batch furnace. Examples of batch furnaces include electric furnaces and rotary kilns. Examples of continuous furnaces include container conveyor tunnel pusher furnaces and roller kilns. When the raw material powder is sintered directly, a continuous furnace is preferred. In a continuous furnace, the container holding the raw material powder can be continuously heated inside the furnace. Since the raw material powder can be sintered without being molded, the nitriding reaction proceeds efficiently. As a result, silicon nitride can be obtained in a short time.
[0063] (Coarse crushing process) In the coarse grinding process, the shaped or powdered silicon nitride obtained from the silicon nitriding process is ground. Grinding can be carried out using, for example, a coarse grinding device, a ball mill, a vibratory mill, etc. Dry grinding is preferred.
[0064] (Micro-pulverization process) In the micro-pulverization process, coarse powder is fed into a media-stirred mill for wet pulverization.
[0065] Wet grinding refers to grinding in a state where coarse powder is mixed with a solvent, i.e., in a slurry state. Water can be used as a solvent, for example.
[0066] The media used in a media-stirred mill can be either metallic or ceramic. From the viewpoint of fully micronizing coarse powder, metallic media is preferred. Iron and steel, which are primarily composed of iron, are preferred metals. Only one type of media can be used, or two or more can be used in combination.
[0067] The coarse powder and solvent can be supplied directly to the media-stirred mill, or a slurry can be prepared in advance and supplied to the media-stirred mill.
[0068] D of silicon nitride powder obtained in the micronization process 50 Even after undergoing acid treatment and cleaning processes, the silicon nitride powder remains essentially unchanged. The D... 50 The preferred size and D of this powder 50 The preferred sizes are the same.
[0069] (Acid treatment process) An acidic solution is added to silicon nitride powder obtained by wet milling to perform acid treatment. By adding an acidic solution to the silicon nitride powder, impurities such as metals and silicon dioxide contained in the silicon nitride powder can be dissolved and removed.
[0070] Examples of acidic substances included in the acidic solution include inorganic acids such as hydrogen fluoride, hydrogen chloride, nitric acid, and sulfuric acid. Hydrochloric acid (an aqueous solution of hydrogen chloride) is preferably used to dissolve the metal contained in the wet-milled silicon nitride powder. Hydrofluoric acid (an aqueous solution of hydrogen fluoride) is preferably used to dissolve the silicon dioxide contained in the wet-milled silicon nitride powder. That is, the acid treatment process is preferably carried out using a mixture of hydrofluoric acid and hydrochloric acid. The acid treatment process can be carried out while stirring the acid treatment slurry containing silicon nitride powder and the acidic solution, or it can be carried out by allowing it to stand without stirring.
[0071] The acid-treated slurry contains acid-treated silicon nitride powder, acidic substances, and impurities. The acid-treated slurry, after acid treatment, is used as the treatment solution to remove the acidic substances and impurities in the next cleaning process.
[0072] The total concentration of acidic substances such as hydrofluoric acid and hydrogen chloride relative to the total mass of the acid-treated slurry is preferably 7.0 to 10.0% by mass, more preferably 7.5 to 9.5% by mass, and even more preferably 8.0 to 9.0% by mass.
[0073] If the concentration of acidic substances is above the aforementioned lower limit, it promotes the dissolution of impurities such as iron and silicon dioxide contained in the silicon nitride powder. If the concentration of acidic substances is below the aforementioned upper limit, the acidic substances can be easily removed by washing.
[0074] The solid component concentration of the acid treatment slurry used as the treatment liquid is preferably 10 to 45% by mass, more preferably 15 to 40% by mass, and even more preferably 20 to 35% by mass.
[0075] The pH of the acid-treated slurry (i.e., the treated liquid) after acid treatment is preferably 0 to 2.0, more preferably 0 to 1.5, and even more preferably 0 to 1.0.
[0076] (Cleaning process) In the cleaning process, the liquid to be treated is fed to a solid-liquid separator, where it is concentrated. After concentration, cleaning liquid is added, and the concentration is repeated. This cleaning operation is performed continuously. As a result, a composition containing silicon nitride powder with reduced acidity and impurities in the treated liquid is obtained.
[0077] A continuous solid-liquid separator is preferred. Examples of continuous solid-liquid separators include cross-flow filtration devices and continuous centrifugal separators.
[0078] Examples of cross-flow filtration devices include a filter-type cross-flow filtration device with a filter membrane as the filter media and a rotary cross-flow filtration device with a filter cloth as the filter media.
[0079] The materials used for components such as filter media that come into contact with the treated liquid only need to be acid-resistant. Examples of acid-resistant resins include ceramics, polyvinylidene fluoride (PVDF), and polypropylene (PP).
[0080] In the cross-flow method, the liquid to be treated flows parallel to the filter surface of the filter media while pressure is applied in a direction from the inside to the outside of the filter surface. As a result, while preventing solid components from accumulating on the inside of the filter surface, the liquid components pass through the filter media, thus concentrating the liquid to be treated.
[0081] The pore size of the filter membrane relative to the D of the silicon nitride powder in the treated liquid 50 Preferably, the ratio is 0.01 to 1.00 times, more preferably 0.02 to 0.50 times, and even more preferably 0.03 to 0.30 times. If the membrane pore size is above or above the lower limit, sufficient filtration flux can be easily obtained; if it is below the upper limit, the ultrafine silicon nitride powder is not easily permeated through the filter membrane, and the amount of solid components in the waste liquid can be easily suppressed.
[0082] The inter-membrane pressure difference of the filter membrane is preferably 0.10 to 0.50 MPa, more preferably 0.15 to 0.40 MPa, and even more preferably 0.20 to 0.30 MPa.
[0083] The air permeability of the filter cloth is preferably 0.10–0.50 cc / cm. 2 •s, more preferably 0.15~0.45cc / cm 2 •s, more preferably 0.20–0.40 cc / cm 2 •s. If the membrane pore size is above the lower limit mentioned above, it is easy to obtain sufficient filtration flux. If it is below the upper limit mentioned above, the ultrafine silicon nitride powder is not easy to pass through the filter membrane, and the amount of solid components in the waste liquid is easily suppressed.
[0084] A continuous centrifuge comprises the following mechanism: a liquid to be processed is continuously supplied to a rotating centrifuge; centrifugal force is applied to perform solid-liquid separation; and the concentrate and separated liquid are discharged from their respective outlets. Commercially available continuous centrifuges can be used. Both horizontal and vertical types are acceptable. Regarding the material of the parts of the continuous centrifuge that come into contact with the liquid to be processed, only acid resistance is required. For example, acid-resistant alloys are suitable, with Hastelloy being preferred.
[0085] The centrifugal force is preferably set such that the solid content concentration of the precipitate formed by centrifugal separation is 65-80% by mass, preferably 68-75% by mass. Water is added at the outlet where the precipitate is discharged, and the concentrate is discharged from the separator as a liquid with a solid content concentration of 20-45% by mass, preferably 30-40% by mass. If the solid content concentration of the concentrate is below the above-mentioned upper limit, the viscosity of the concentrate can be reduced, improving the liquid delivery to the next process.
[0086] The centrifugal force (centrifugal acceleration) of the separator is preferably 1000 to 3000 G, more preferably 2000 to 2500 G.
[0087] The coagulant used in the coagulation filtration process is preferably an inorganic coagulant. As an inorganic coagulant, it is preferably one or more selected from the group consisting of ammonium sulfate, ammonium acetate, aluminum sulfate, and ferric sulfate.
[0088] The preferred method for adding the coagulant is to add an aqueous coagulant solution to the liquid being treated. If the concentration of the coagulant (unit: mass%, hereinafter also referred to as "addition concentration") relative to the mass of the aqueous coagulant solution is too high, the residue in the dried silicon nitride powder will be high; if it is too low, sufficient coagulation effect cannot be obtained. Therefore, it is preferable to be within a range that does not cause these adverse conditions. For example, it is preferably 0.005 to 0.15% by mass, more preferably 0.01 to 0.14% by mass, and even more preferably 0.05 to 0.13% by mass.
[0089] The pH of the liquid being treated in the coagulation filtration process preferably includes at least a portion of the pH region where the dispersibility of silicon nitride powder is improved.
[0090] If the dispersibility of silicon nitride powder in the treated liquid is improved, the filter media will become clogged when the pore size is small, resulting in a decrease in filtration throughput. If the filter media has a large pore size, the silicon nitride powder will pass through the filter media, increasing the amount of solid components in the waste liquid.
[0091] By adding a coagulant to the treated liquid in a pH region with improved dispersibility to promote coagulation, it is possible to achieve increased filtration flux, reduced solid content in the waste liquid, or both.
[0092] The pH range in which silicon nitride powder exhibits improved dispersibility varies depending on the manufacturing method of the silicon nitride powder.
[0093] In the cleaning process of this embodiment, it is preferable to perform a first step using water as the cleaning liquid, followed by a second step (coagulation and filtration step) using a coagulant aqueous solution as the cleaning liquid, and then a third step using an alkaline solution as the cleaning liquid for cleaning and neutralization.
[0094] Examples of alkaline solutions include ammonia solution, sodium hydroxide solution, and calcium hydroxide solution. Among these, ammonia solution is preferred for its low residue in the dried silicon nitride powder. The pH of the alkaline solution is preferably 9 to 12, more preferably 10 to 11.
[0095] The pH of the liquid being treated at the beginning of the first step can be the same as the pH of the slurry at the end of the acid treatment step.
[0096] The pH of the treated liquid at the end of the first step is the same as the pH of the treated liquid at the beginning of the second step, preferably within the same range as the pH of the treated liquid at the beginning of the coagulation and filtration step described above.
[0097] The pH of the treated liquid at the end of the second step is the same as the pH of the treated liquid at the beginning of the third step, preferably within the same range as the pH of the treated liquid at the end of the above-mentioned coagulation and filtration step.
[0098] The pH (endpoint) of the treated liquid at the end of the third step is preferably 7 to 10, more preferably 8 to 9.
[0099] It should be noted that after the second step, the third step, which uses an alkaline solution, can be replaced by simply supplying water for rinsing until the aforementioned pH (endpoint) is reached. However, considering the need to shorten the treatment time and reduce the amount of waste liquid, the third step is preferred.
[0100] The solid component concentration of the composition containing silicon nitride powder after the cleaning process is preferably 15 to 40% by mass, more preferably 20 to 35% by mass. If it is above the lower limit, it is preferred in terms of reducing the heat energy required for drying, and if it is below the upper limit, it is preferred in terms of liquid delivery to the next process.
[0101] <Drying Process> The composition containing silicon nitride powder obtained in the cleaning process is dried to obtain silicon nitride powder. The drying temperature is preferably 100-140°C, more preferably 110-130°C. The drying time is preferably 40-180 minutes, more preferably 60-120 minutes.
[0102] <Uses> The silicon nitride powder of this embodiment has a small average particle size, resulting in excellent sinterability. Therefore, silicon nitride powder can be used as a sintering raw material for silicon nitride sintered bodies. Furthermore, as shown in the examples described later, sintered bodies with excellent insulation and heat dissipation properties can be manufactured.
[0103] <Method for manufacturing silicon nitride sintered bodies> One embodiment of the method for manufacturing a silicon nitride sintered body includes: a step of forming a sintering raw material containing the powder to manufacture a shaped body; and a step of firing.
[0104] In addition to silicon nitride powder (this powder), the sintering raw material may also contain oxide-based sintering aids. Examples of oxide-based sintering aids include yttrium oxide, magnesium oxide, and aluminum oxide. The content of oxide-based sintering aids in the sintering raw material is, for example, 3 to 10% by mass.
[0105] In the process of manufacturing the molded body, for example, a molding pressure of 3.0 to 30 MPa is applied to obtain the molded body. The molded body can be manufactured by uniaxial pressing or by CIP (Cold Isostatic Pressing) molding. Alternatively, it can be formed by hot pressing while firing.
[0106] The firing of the molded body can be carried out in an inert gas atmosphere such as nitrogen or argon. The firing pressure can be 0.7 to 1 MPa. The firing temperature is preferably 1860 to 2100°C, more preferably 1880 to 2000°C. The firing time at the aforementioned firing temperature is preferably 6 to 20 hours, more preferably 8 to 16 hours. The heating rate up to the firing temperature is preferably, for example, 1.0 to 10.0°C / min.
[0107] Silicon nitride sintered bodies made using this powder exhibit excellent insulation and heat dissipation properties.
[0108] For example, a silicon nitride sintered body with an insulation breakdown voltage of 5 kV or more, preferably 9 kV or more, as measured by the method described in the embodiments described later, is obtained.
[0109] For example, a silicon nitride sintered body with a thermal conductivity of 50 W / (m·K) or more, preferably 70 W / (m·K) or more, as measured by the method described in the embodiments described below, is obtained.
[0110] Example The present invention will be further described in detail below using examples, but the present invention is not limited to these examples.
[0111] (Zeta potential, isoelectric point) The isoelectric point was determined by measuring the zeta potential using a high-concentration particle size zeta potential measuring device (Colloidal Dynamics product name "AcoustoSizer IIx") based on the electroacoustic method. Specifically, a dispersion containing silicon nitride powder was prepared using the following method, and this dispersion was placed as a sample in the measuring device while the pH was changed to measure the zeta potential.
[0112] [Sample Preparation] Water was added to the powder of the test object to prepare a 5% by mass slurry. After dispersion using a commercially available dispersion device, the test was performed.
[0113] [Measurement Conditions] • Measurement environment: Room temperature (23.0℃), humidity 34% • Measurement mode: Polar mode • Analysis mode: Lognomal • Measurement method: Potentiometric titration (pH=1, 1.5, 2, 2.5, 3, 4, 5, 6) • Mixing speed: 110 rpm • Cycling speed: 140 rpm Titrant: 1M hydrochloric acid • Other: Stir the sample before measurement and then shake it.
[0114] (D) 50 ) D 50 The particle size distribution was determined using laser diffraction and scattering. The determination was performed in accordance with the method described in JIS R 1629:1997 "Method for determination of particle size distribution of fine ceramic raw materials based on laser diffraction and scattering".
[0115] D of silicon nitride powder after cleaning process 50 The determination was performed using the method described above. In the determination, 60 mg of the target powder was measured into a 500 mL container. 2 mL of a 20% (w / w) aqueous solution of sodium hexametaphosphate (as a dispersant) and 200 g of water were added to prepare a dispersion. The container was placed in an ultrasonic disperser (manufactured by Sharp Corporation) with the dispersion completely immersed, and ultrasonic dispersion was performed for 1 minute. The particle size distribution of the ultrasonically dispersed sample was then determined as described above.
[0116] The D of silicon nitride powder contained in the treatment liquid 50 In this case, the silicon nitride slurry before the addition of the acidic solution (the silicon nitride slurry after wet micronization) is dried and pulverized, and then the silicon nitride powder after the above-mentioned cleaning process is used for D... 50 The same method was used for determination.
[0117] (Specific surface area) Regarding the BET specific surface area of silicon nitride powder, the determination was performed using nitrogen and the BET single-point method, following JIS R 1626:1996 "Determination of specific surface area of fine ceramic powders based on gas adsorption BET method". It should be noted that the wet-milled silicon nitride slurry was thoroughly dried using a shed dryer, then pulverized in a mortar and pestle before being measured using the above method. The composition containing silicon nitride powder after acid treatment and cleaning was dried using a spray dryer before being measured using the above method.
[0118] (Content of chlorine, fluorine, oxygen and iron) The chlorine and fluorine content of silicon nitride powder was determined using the method described above. Specifically, the silicon nitride powder was heated using an automated sample combustion apparatus (Mitsubishi Chemical Corporation, AQF-2100H type) to dissolve the generated gas in water. Ion chromatography (Thermo Fisher Scientific Inc., ICS-2100 type) was used to determine the Cl and F ions in the water. Based on the measured values, the chlorine (Cl) and fluorine (F) content of the silicon nitride powder was calculated.
[0119] Regarding the oxygen content of silicon nitride powder, the above method is used to determine the total oxygen content. Specifically, using an oxygen and nitrogen analyzer (manufactured by Horiba Manufacturing Co., Ltd., device name: EMGA-920), the silicon nitride powder is heated from 20°C to 2000°C in a helium atmosphere at a heating rate of 8°C / second, and the amount of oxygen released is quantified to determine the total oxygen content (mass%) of the silicon nitride powder.
[0120] The iron content of the silicon nitride powder was determined using a fluorescence X-ray analysis device (manufactured by Rigaku Corporation, device name: PrimasII).
[0121] Regarding the iron content in the treatment solution, after drying and pulverizing the silicon nitride slurry (silicon nitride slurry after wet micronization) before adding the acidic solution, the iron content was determined using the same method as that used for the silicon nitride powder described above.
[0122] (α-conversion rate) The α-saturation rate was determined using the method described above. The XRD pattern was obtained by X-ray powder diffraction. Specifically, using an X-ray powder diffraction apparatus (manufactured by Rigaku Corporation, apparatus name: UltimaIV), the target powder was filled onto a dedicated substrate, and a Cu-K α-line source was used. The diffraction was performed under the conditions of a diffraction angle of 2θ = 10 to 80°, a sampling width of 0.02°, and a scanning speed of 10° / min, thereby obtaining the XRD pattern. Then, using the comprehensive powder X-ray analysis software "Rietveld Method Software (manufactured by MDI Corporation, comprehensive powder X-ray software Jade+9)," the α-saturation rate was calculated using Equation 1 above, based on the intensity of the diffraction peaks of the (102) plane of the α phase of silicon nitride, the (210) plane of the α phase of silicon nitride, the (102) plane of the β phase of silicon nitride, and the (210) plane of the β phase of silicon nitride.
[0123] (Solid components) The concentration of solid components in the treated liquid (unit: mass%) is calculated by the formula: (weight of silicon nitride powder supplied for wet grinding) ÷ (weight of silicon nitride slurry obtained by wet grinding + weight of the mixture of hydrofluoric acid and hydrochloric acid added to the aforementioned silicon nitride slurry) × 100.
[0124] The amount of solids in the waste liquid (unit: mg / L) was determined according to the method for determining the concentration of suspended solids specified in JIS K 0102:2019 "Test Methods for Factory Wastewater". Specifically, the waste liquid to be tested was filtered through filter paper with a pore size of 1 μm and a diameter of 25–50 mm. The dry weight of the substance remaining on the filter paper was divided by the volume of the filtered liquid to obtain the amount of solids (unit: mg / L).
[0125] <Manufacturing Example 1: Preparation of the Treated Liquid> The treated liquid used in each example was prepared by generating silicon nitride using a direct nitriding method, wet pulverizing it to obtain a slurry containing silicon nitride powder (silicon nitride slurry), and then further acid-treated.
[0126] Specifically, a molded body (bulk density: 1.4 g / cm³) was fabricated using metallic silicon powder. 3 The resulting molded body was placed in an electric furnace and fired at 1400°C for 60 hours to obtain a fired body containing silicon nitride. A mixture of nitrogen and hydrogen (a mixture of N2 and H2 at a volume ratio of 80:20 under standard conditions) was supplied as the firing atmosphere. The fired body was then pulverized using a dry jaw crusher and subsequently pulverized using a dry ball mill to obtain coarse powder containing silicon nitride.
[0127] The obtained coarse powder is fed into a media-stirred mill, where it is wet-milled using water as a solvent to obtain a silicon nitride slurry containing silicon nitride powder. The media material of the media-stirred mill is set to an iron-containing alloy.
[0128] The resulting silicon nitride slurry contains at least iron as an impurity, in addition to silicon nitride powder.
[0129] The silicon nitride slurry obtained by wet grinding is placed in an acid treatment tank, a mixture of hydrofluoric acid and hydrochloric acid is added, and the mixture is stirred at room temperature for 6 hours to carry out acid treatment, thus obtaining the treated liquid.
[0130] In addition to the acid-treated silicon nitride powder, the treated liquid also contains acidic substances used in the acid treatment and at least iron as an impurity.
[0131] Table 1 shows the concentration of solid components, hydrochloric acid content, hydrofluoric acid content, iron content (Fe content), and D of silicon nitride powder in the treated liquid used in each example. 50 The hydrochloric acid and hydrofluoric acid content of the treated liquid are calculated based on the content of acidic substances in the acidic solution used in the acid treatment process.
[0132] <Example 1> In this example, a cross-flow filtration device with ceramic membrane as the filter media is used to separate the solid and liquid components of the liquid to be treated and to perform a cleaning process.
[0133] The ceramic membrane is a tubular membrane made of alumina with a pore size of 0.1 μm.
[0134] Specifically, 1m³ of liquid is contained in the storage tank of the filtration device. 3 The liquid to be treated is continuously supplied from the storage tank to the filter media. The permeate that passes through the filter media is removed as waste liquid, and the concentrate that does not pass through the filter media is returned to the storage tank, thus circulating the liquid.
[0135] While the treated liquid is being supplied to the filter media, water is supplied in a manner that keeps the liquid volume in the storage tank constant. That is, water is added to the concentrate returned to the storage tank, and the solution is concentrated again using the filter media; this operation is repeated continuously. In this manner, the filter media is rinsed with water until the pH of the liquid supplied to the filter media reaches 1 (Step 1). The average filtration flux of Step 1 is shown in Table 1 (hereinafter, the same applies). Next, instead of water, a 0.05% by mass ammonium sulfate aqueous solution, used as a coagulant, is supplied to the storage tank in a manner that keeps the liquid volume in the storage tank constant. In this manner, the filter media is rinsed while adding the coagulant until the pH of the liquid supplied to the filter media reaches 3 (Step 2). The average filtration flux in Step 2 is shown in Table 1 (hereinafter, the same applies).
[0136] Next, instead of the coagulant aqueous solution, a 0.08% by mass ammonia solution is supplied to the storage tank in such a way that the liquid volume in the storage tank becomes constant. In this manner, neutralization and rinsing with the ammonia solution are performed until the pH of the liquid supplied to the filter media reaches 9 (Step 3). The average filtration flux in Step 3 is shown in Table 1 (hereinafter, the same applies).
[0137] After the pH of the liquid supplied to the filter media reaches 9, the supply of liquid to the storage tank is stopped, resulting in a cleaned composition containing silicon nitride powder. The solid component concentration of the composition containing silicon nitride powder is the same as that of the treated liquid.
[0138] The composition containing silicon nitride powder obtained in the cleaning process is dried at 300°C to obtain silicon nitride powder after the cleaning process.
[0139] The total waste liquid volume, solid component content in the waste liquid, overall average filtration flux, and treatment capacity of all processes are shown in Table 1 (the same applies below).
[0140] The amount of solid components in the waste liquid was determined using the method described above. The total waste liquid volume is defined as the sum of the total water supply in the first process, the total coagulant aqueous solution supply in the second process, and the total ammonia aqueous solution supply in the third process. Treatment capacity refers to the capacity to treat 1 m³ of waste liquid. 3 The required processing time for the treated liquid is defined as the sum of the processing times for steps 1, 2, and 3 (total processing time). The overall average filtration flux is calculated by dividing the total waste liquid volume by the filter media area and then dividing the total processing time.
[0141] The Zeta potential of the obtained silicon nitride powder was measured using the method described above. Table 2 shows the Zeta potential at the isoelectric point and pH 1.5 (referred to as "Zeta potential (pH 1.5)" in the table), the pH at which the maximum positive Zeta potential is achieved (referred to as "pH at maximum potential" in the table), and the maximum positive Zeta potential (referred to as "maximum positive potential" in the table).
[0142] Table 2 shows the D of the obtained silicon nitride powder. 50 Specific surface area, iron content (Fe content), oxygen content, and α-susceptibility (the same applies below). The D-value of the dried silicon nitride powder. 50 D with silicon nitride powder in the treated liquid 50 Same. It was confirmed that iron, which is an impurity, in the treated liquid was significantly removed.
[0143] <Example 2> In this example, a cross-flow filtration device with a resin membrane as the filter media is used to separate the solid and liquid components of the liquid to be treated and to perform a cleaning process.
[0144] The resin membrane is made of polyvinylidene fluoride (PVDF), with a pore size of 0.1 μm, an inner diameter of 1.4 mm, and a filter media area (effective filtration area) of 7.9 m². 2 Hollow fiber membrane.
[0145] The same procedure as in Example 1 was followed, performing steps 1, 2, and 3 to obtain a cleaned composition containing silicon nitride powder. The obtained composition containing silicon nitride powder was then dried in the same manner as in Example 1 to obtain cleaned silicon nitride powder.
[0146] <Example 3> In this example, a rotary cross-flow filter is used to separate the solid and liquid components of the liquid to be treated and to perform a cleaning process.
[0147] The filter media has an air permeability of 0.3cm.3 / cm 2 ·s polypropylene filter cloth (double-layer fabric).
[0148] The same procedure as in Example 1 was followed, performing steps 1, 2, and 3 to obtain a cleaned composition containing silicon nitride powder. The obtained composition containing silicon nitride powder was dried in the same manner as in Example 1 to obtain cleaned silicon nitride powder.
[0149] <Comparative Example 1> Commercially available silicon nitride powder was used as the test subject, and the items listed in Table 2 were measured. The results are shown in Table 2.
[0150] <Evaluation of Silicon Nitride Sintered Bodies> [Manufacturing of silicon nitride sintered bodies] To 91.4 parts by weight of silicon nitride powder prepared in each example, 6.0 parts by weight of Y₂O₃ and 1.5 parts by weight of MgO as sintering aids were added, along with organic solvents, organic binders, plasticizers, etc., and the mixture was uniformly mixed using a ball mill to form a raw material slurry. After degassing and thickening the raw material slurry, a sheet was formed using a doctor blade coating method to obtain a molded body. After cutting the obtained sheet molded body, it was degreased in air at 500°C, and then fired in a firing furnace at 1850°C in a nitrogen atmosphere for 5 hours to produce a silicon nitride sintered body.
[0151] [Evaluation of silicon nitride sintered bodies: Insulation] The silicon nitride sintered body was ground to produce a 50mm × 50mm × 0.3mm cuboid for measuring the insulation breakdown voltage. The insulation breakdown voltage was measured at room temperature in accordance with JIS C 2110-1:2016. The results are shown in Table 2.
[0152] The evaluation criteria for insulation are as follows.
[0153] A: The insulation breakdown voltage is above 9kV.
[0154] B: The insulation breakdown voltage is above 5kV and less than 9kV.
[0155] C: Insulation breakdown voltage is less than 5kV.
[0156] The silicon nitride sintered body was ground to produce a 50mm × 50mm × 1.0mm cuboid for thermal conductivity measurement. Thermal diffusivity and specific heat capacity were measured using the laser scintillation method (in accordance with JIS R 1611:2010). The product of the density, thermal diffusivity, and specific heat capacity of the sintered body was calculated as the thermal conductivity at room temperature. The results are shown in Table 2.
[0157] The evaluation criteria for thermal conductivity are as follows.
[0158] A: Thermal conductivity is above 70 W / (m·K).
[0159] B: Thermal conductivity is above 50 W / (m·K) and less than 70 W / (m·K).
[0160] C: Thermal conductivity less than 50 W / (m·K).
[0161] [Table 1] [Table 2] In any of the filtration devices in Examples 1 to 3, no corrosion was observed in the parts in contact with the treated liquid, indicating good acid resistance.
[0162] As shown in Table 2, the silicon nitride sintered bodies manufactured using the silicon nitride powders of Examples 1 to 3 exhibit excellent insulation and heat dissipation properties.
[0163] On the other hand, regarding the silicon nitride powder of Comparative Example 1, its isoelectric point is 3, and the silicon nitride sintered body made using it has poor insulation and heat dissipation.
Claims
1. Silicon nitride powder, which has an isoelectric point at pH 7–9.
2. The silicon nitride powder as described in claim 1, wherein the α-saturation rate is 90-97%.
3. The silicon nitride powder as described in claim 1, wherein, The pH at which the maximum positive Zeta potential is reached is 2–4.
4. The silicon nitride powder as described in claim 3, wherein, The Zeta potential at pH 1.5 is 30–45 mV.
5. A method for manufacturing silicon nitride sintered bodies, wherein, The sintering raw material containing silicon nitride powder as described in any one of claims 1 to 4 is shaped and sintered.
Citation Information
Patent Citations
Aluminum-ceramic joint substrate
JP2011077546A
Information processing system, information processing device, and information processing method
JP2024057571A
